A Spectraplakin Is Enriched on the Fusome and Organizes Microtubules during Oocyte Specification in Drosophila. - Roper, K.; Brown, N.H. (Current Biology, 2004)
During Drosophila oogenesis a membranous organelle called the fusome has a key function in the establishment of oocyte fate and polarity, ultimately leading to the establishment of the major body axes of the animal. The fusome is necessary for the microtubule-driven restriction of markers of oocyte fate to the oocyte, but the mechanism by which the fusome organizes the microtubules is not known.We have identified the spectraplakin Short stop (Shot) as a new component of the fusome. Spectraplakins are giant cytoskeletal linker proteins, with multiple isoforms produced from each gene. Shot is the sole spectraplakin in Drosophila. The phenotype caused by the absence of Shot is not similar to that of other components of the fusome but instead is similar to the absence of the downstream components that interact with microtubules: the dynein/dynactin-complex-associated proteins Egalitarian and BicaudalD. Shot is required for the association of microtubules with the fusome and the subsequent specification of the oocyte in 16-cell cysts. Shot is also required for the concentration of centrosomes into the oocyte, a process thought to be independent of microtubules because it still occurs in the presence of microtubule depolymerizing drugs. This suggests that Shot may protect some microtubules from depolymerization and that these microtubules are sufficient for this process.Shot provides the missing link between the fusome and microtubules within meiotic cysts, which is essential for the establishment of the oocyte. Shot associates with the fusome and is required for microtubule organization. We suggest that it does this directly, via its microtubule binding GAS2 domain.